2016
DOI: 10.3390/genes7060023
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Role of KIBRA and PTPN14 in Hippo Signaling and Beyond

Abstract: The Hippo signaling pathway regulates cellular proliferation and survival, thus exerting profound effects on normal cell fate and tumorigenesis. Pivotal effectors of this pathway are YAP/TAZ, transcriptional co-activators whose dysfunction contributes to the development of cancer. Complex networks of intracellular and extracellular signaling pathways that modulate YAP and TAZ activities have recently been identified. Among them, KIBRA and PTPN14 are two evolutionarily-conserved and important YAP/TAZ upstream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Hence, the reduced expression of Hippo core kinases in the +DDR/+COL1 HT1080 tumours may underlie the ability of these tumours to display accelerated growth. Consistent with the tumour suppressive role of the Hippo pathway, we found that KIBRA, an upstream regulator of the Hippo pathway, and also considered a tumour suppressor [150][151][152][153] , was significantly downregulated in +DDR2/+COL1 but not in +DDR1b/+COL1 tumours. This suggests that KIBRA may be a major target of DDR2 signalling in response to collagen in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, the reduced expression of Hippo core kinases in the +DDR/+COL1 HT1080 tumours may underlie the ability of these tumours to display accelerated growth. Consistent with the tumour suppressive role of the Hippo pathway, we found that KIBRA, an upstream regulator of the Hippo pathway, and also considered a tumour suppressor [150][151][152][153] , was significantly downregulated in +DDR2/+COL1 but not in +DDR1b/+COL1 tumours. This suggests that KIBRA may be a major target of DDR2 signalling in response to collagen in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…Among this small group of transcripts were several whose encoded proteins might participate in the accelerated growth of recurrent tumors (Supplemental Figure S1A). These included Gdf3, a member of the TGF-β family of growth factors, which was up-regulated (58); Ildr2, Pcx and Dhtkd1, which regulate lipid and carbohydrate metabolism and which were all down-regulated (59-61); and three putative tumor suppressors, PLK2, PTPN14, and TSHZ2, which were also down-regulated (62)(63)(64).…”
Section: Resultsmentioning
confidence: 99%
“…There are now many reports of mutation of PTPN14 in several different human tumors (42)(43)(44)(45) and clear evidence for a role for PTPN14 in the control of diverse signaling pathways. This includes regulation of the Hippo pathway, ␤-catenin signaling, and transforming growth factor ␤ (TGF-␤) and receptor trafficking (30,31,38,46). Currently, we have no information on which of these pathways are likely to be affected as a result of E7-induced degradation of PTPN14, although our preliminary unpublished results would appear to indicate that the Hippo pathway is not directly affected by E7.…”
Section: Discussionmentioning
confidence: 99%